Virgil, Aeneid 11 : a commentary - Virgil. (Mnemosyne, Supplements, 2003)
This is the first comprehensive commentary on Aeneid 11. The commentary treats fully matters of linguistic and textual interpretation, metre and prosody, grammar, lexicon and idiom, of Roman behaviour, social and ritual, as well as Virgil's sources and the literary tradition. New critical approaches and developments in Virgilian studies have been taken into account with economy and fairness. The Latin text is presented with a facing English translation. The commentary is followed by an appendix on Penthesilea and the Epic Cycle and a second appendix which discusses the weaknesses of Aeneid 11. The book concludes with English and Latin indices. In approach and learning, this commentary continues Nicholas Horsfall's impressive work as a commentator and will advance our understanding of the Aeneid and the poet Virgil.